2016
DOI: 10.1016/j.jfma.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of spinal tuberculosis

Abstract: Spinal tuberculosis (STB) is a common manifestation of extrapulmonary tuberculosis (TB). STB accounts for around 2% of all cases of TB and around 15% of extrapulmonary TB cases. The World Health Organization has proposed a global strategy and targets for TB prevention, care, and control after 2015. Under this strategy, patients will receive standard care according to the recommendations and guidelines after confirmation of STB diagnosis. However, current recommendations and guidelines focus on disease and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 65 publications
0
66
1
14
Order By: Relevance
“…Regarding the cases who underwent for both modalities, spinal compression, intravertebral collection, and disc space involvement are better recognized by MRI than CT scan with significant P values. Future research questions need to emphasizeon early identification of Tuberculous Spondylitis and differentiating it from other inflammatory and degenerative spinal diseases [29]. Access of ambulatory patients with suspected spinal pain to MRI or CT scan can be delayed for months.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the cases who underwent for both modalities, spinal compression, intravertebral collection, and disc space involvement are better recognized by MRI than CT scan with significant P values. Future research questions need to emphasizeon early identification of Tuberculous Spondylitis and differentiating it from other inflammatory and degenerative spinal diseases [29]. Access of ambulatory patients with suspected spinal pain to MRI or CT scan can be delayed for months.…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms are usually insidious, there may be complaints that have been going on for years before diagnosis (1) . Low back pain, fever, weight loss, and night sweats are the most common symptoms (10) . The diagnosis usually can be made on the basis of predisposing factors, history of TB disease, clinical findings and imaging methods (1) .…”
Section: Diagnosismentioning
confidence: 99%
“…although studies by Chen et al [14] and Kandala et al [15] showed a male preponderance. In the present study, the mean age of HIV-positive patients with spinal TB was 47 years, and the mean age of HIV-negative patients was 35 years.…”
mentioning
confidence: 93%